Rhizosphere 16S-ITS Metabarcoding Profiles in Banana Crops Are Affected by Nematodes, Cultivation, and Local Climatic Variations - Ciancio, Aurelio; Rosso, Laura Cristina; Lopez-Cepero, Javier; Colagiero, Mariantonietta (Frontiers in Microbiology, 2022)
Agriculture affects soil and root microbial communities. However, detailed knowledge is needed on the effects of cropping on rhizosphere, including biological control agents (BCA) of nematodes. A metabarcoding study was carried out on the microbiota associated with plant parasitic and other nematode functional groups present in banana farms in Tenerife (Canary Islands, Spain). Samples included rhizosphere soil from cv Pequeña Enana or Gruesa and controls collected from adjacent sites, with the same agroecological conditions, without banana roots. To characterize the bacterial communities, the V3 and V4 variable regions of the 16S rRNA ribosomal gene were amplified, whereas the internal transcribed spacer (ITS) region was used for the fungi present in the same samples. Libraries were sequenced with an Illumina MiSeq™ in paired ends with a 300-bp read length. For each sample, plant parasitic nematodes (PPN) and other nematodes were extracted from the soil, counted, and identified. Phytoparasitic nematodes were mostly found in banana rhizosphere. They included Pratylenchus goodeyi, present in northern farms, and Helicotylenchus spp., including H. multicinctus, found in both northern and southern farms. Metabarcoding data showed a direct effect of cropping on microbial communities, and latitude-related factors that separated northern and southern controls from banana rizosphere samples. Several fungal taxa known as nematode BCA were identified, with endophytes, mycorrhizal species, and obligate Rozellomycota endoparasites, almost only present in the banana samples. The dominant bacterial phyla were Proteobacteria, Actinobacteria, Planctomycetes, Bacteroidetes, Chloroflexi, and Acidobacteria. The ITS data showed several operational taxonomic units (OTUs) belonging to Sordariomycetes, including biocontrol agents, such as Beauveria spp., Arthrobotrys spp., Pochonia chlamydosporia, and Metarhizium anisopliae. Other taxa included Trichoderma harzianum, Trichoderma longibrachiatum, Trichoderma virens, and Fusarium spp., together with mycoparasites such as Acrostalagmus luteoalbus. However, only one Dactylella spp. showed a correlation with predatory nematodes. Differences among the nematode guilds were found, as phytoparasitic, free-living, and predatory nematode groups were correlated with specific subsets of other bacteria and fungi. Crop cultivation method and soil texture showed differences in taxa representations when considering other farm and soil variables. The data showed changes in the rhizosphere and soil microbiota related to trophic specialization and specific adaptations, affecting decomposers, beneficial endophytes, mycorrhizae, or BCA, and plant pathogens.